BERBAGAI TEKNIK PENGOLAHAN TERHADAP KUALITAS IKAN TONGKOL (Eutynnus sp) AFKIR SEBAGAI PAKAN TERNAK - Evi Irawati; Mirzah Mirzah; R. Saladin (Jurnal Peternakan, 2014)
Rejected little tuna (Eutynnus sp) is alternative feed ingredient which same quality to commercial fish meal and the price is relatively cheaper. The aim of this research were to study the interaction between the salt level with time of steaming on the nutritional content (dry matter, crude protein, extract ether, crude fiber, calcium and phosphorus) of rejected little tuna meal. The experimental design was completely randomized design (CRD) 3 x 3 factorial pattern with 3 replications. The first factor was level of salting (A) (A1 = 2.5 %, A2 = 5.0%, A3 = 7.5%) the second factor was times of steaming (B) (B1 = 15 min, B2 = 30 min, B3 = 45 minutes). The results showed that the interaction between the level of salt to the time of steaming can maintain quality of rejected little tuna fish processed, it was seen with increasing of nutrient content of crude protein of rejected little tuna (50.16-64.42%), and the processing of rejected little tuna by salting and steaming highly significant effect (P <0.01) and there is a higly significant interaction (P <0.01) through the on dry matter and extract ether rejected little tuna processed. In conclusion, the processing of rejected little tuna by salting and steaming can maintain quality of rejected little tuna, it was seen with increasing of nutrient especially on crude protein (50.16-64.42), so that it can be used as animal feed.